Raspberry Pi 3 Cookbook for Python Programmers: Unleash the Potential of Raspberry Pi 3 with over 100 Recipes - Fernandes, Steven Lawrence; Cox, Tim (Packt Publishing, Limited, 2018)
Raspberry Pi 3 is a tiny affordable chip used to learn and program through interactive projects. It has gained a lot of traction as the first choice in single-board computers due to its versatility. It extends a wide range of support to Python programming. This recipe-based guide will allow you to showcase the capabilities of Raspberry Pi 3.